In Vivo Verification of Electron Paramagnetic Resonance Biodosimetry Using Patients Undergoing Radiation Therapy Treatment - Draeger, Emily; Roberts, Kenneth; Decker, Roy D.; Bahar, Nina; Wilson, Lynn D.; Contessa, Joseph; Husain, Zain; Williams, Benjamin B.; Flood, Ann Barry; Swartz, Harold M.; Carlson, David J. (International journal of radiation oncology, biology, physics, 2024)
Electron paramagnetic resonance (EPR) biodosimetry, used to triage large numbers of individuals incidentally exposed to unknown doses of ionizing radiation, is based on detecting a stable physical response in the body that is subject to quantifiable variation after exposure. In vivo measurement is essential to fully characterize the radiation response relevant to a living tooth measured in situ. The purpose of this study was to verify EPR spectroscopy in vivo by estimating the radiation dose received in participants’ teeth. A continuous wave L-band spectrometer was used for EPR measurements. Participants included healthy volunteers and patients undergoing head and neck and total body irradiation treatments. Healthy volunteers completed 1 measurement each, and patients underwent measurement before starting treatment and between subsequent fractions. Optically stimulated luminescent dosimeters and diodes were used to determine the dose delivered to the teeth to validate EPR measurements. Seventy measurements were acquired from 4 total body irradiation and 6 head and neck patients over 15 months. Patient data showed a linear increase of EPR signal with delivered dose across the dose range tested. A linear least-squares weighted fit of the data gave a statistically significant correlation between EPR signal and absorbed dose (P < .0001). The standard error of inverse prediction (SEIP), used to assess the usefulness of fits, was 1.92 Gy for the dose range most relevant for immediate triage (≤7 Gy). Correcting for natural background radiation based on patient age reduced the SEIP to 1.51 Gy. This study demonstrated the feasibility of using spectroscopic measurements from radiation therapy patients to validate in vivo EPR biodosimetry. The data illustrated a statistically significant correlation between the magnitude of EPR signals and absorbed dose. The SEIP of 1.51 Gy, obtained under clinical conditions, indicates the potential value of this technique in response to large radiation events.